The Metabolic Flexibility of Staphylococcus Aureus: Linking Nutrient Adaptation to Persistence and Pathogenicity - ALSAHOO, Raed Amer ali (American Journal of Biology and Natural Sciences, 2025)
Staphylococcus aureus is a human commensal that can provoke mild localized infections, as well as disperse to cause a range of severe diseases, including endocarditis, pneumonia, and sepsis. Its ability to infect such a diverse array of host‐derived microenvironments implicates a remarkable metabolic flexibility that allows it to optimize growth in the face of nonpreferred carbon sources, potential nutrient starvation, and persisting host inflammation. In addition to broad nutrient utilization, adaptive rewiring of central metabolic pathways contributes to S. aureus survival and persistence. The metabolic determinants of persistence apparently connect with full pathogenicity, suggesting that metabolic adaptation also supports virulence during infection . Metabolic cross talk between host and pathogen follows three major steps: sensing, adapting, and competing. One feature of many host–pathogen interactions is the first step in that the two parties typically regulate gene expression and enzyme or transporter activity in response to changes in nutrient availability. Consequently, growth and virulence follow the available nutrient supply. For S. aureus, this means that central metabolism fuels the generation of precursors for protein biogenesis, energy conservation, and therefore growth. Discrete metabolic pathways also produce activated cofactors such as NAD^+, NADP^+, and FAD^++, whose levels orchestrate carbon flux through central metabolic pathways. Since a high degree of cellular fitness is required to maintain pathogenesis, pathogens must adjust their central metabolic pathways to suit their carbon source.